The Relation of Brinkman Index and Body Mass Index with Spirometry Result of Chronic Obstructive Pulmonary Disease (COPD) Outpatients in the Pulmonology and Respiratory Medicine Department of Zainoel Abidin General Hospital - Raina Muzlifa; Mulyadi Mulyadi; Husnah Husnah (World Nutrition Journal, 2022)
Background: Chronic Obstructive Pulmonary Disease (COPD) is one of the major health problems worldwide. Smoking is the main risk factor of the COPD development. Not only COPD has clinical manifestations in the lungs, it also manifest outside lungs called systemic effects.One of systemic effects found in COPD patients is weight loss leading to declining lung function. This study aims to determine the relation of Brinkman Index and Body Mass Index (BMI) with spirometry result of COPD outpatients in RSUDZA. Methods: The study was held in lung outpatients department in RSUDZA Banda Aceh on December 5th until 28th with cross sectional design The sampling method is nonprobability sampling with accidental sampling technique. Respondents consisted of 30 patients who had agreed to informed consent given. Medical record used to obtain Brinkman index, BMI, and spirometry result of the patients. Results: The results of analysis shows majority of respondents are male (83,3%), dominated by 56-65 years age range (40,0%) and had moderate Brinkman Index (46,7%). The majority of respondents (53,3%) had an abnormal BMI (severe underweight (13,3%), underweight (6,7%), overweight (23,3%), and obese (10,0%)) and severe spirometry result (53,3%). The data was analyzed by the Spearman Correlation. With the Spearman Correlation, there was no association between Brinkman Index and spirometry result with p value 0,412 (p value >0,05). Meanwhile, there was an association between the BMI and spirometry result with p value 0,006 (p < 0,05). The strength of the correlation is moderate (rs =-0,488). Conclusion: The lower the BMI, the more severe the spirometry result.